From Competition State to Green Entrepreneurial State: New challenges for Denmark - Voldsgaard, Asker; Mazzucato, Mariana; Conway, Rowan (Samfundsøkonomen, 2022)
The 2019 Danish Climate Law marks a shift from the growth-focused competition state towards a mission-oriented entrepreneurial state that promises to bring the Danish way of life within planetary boundaries. In this article, we analyse the institutional challenges that arise when reorienting the state in this direction.